Peningkatan Hasil Belajar Matematika Melalui Strategi Pembelajaran Problem Based Learning (PBL) Pada Siswa Kelas VII A Semester Genap SMP Negeri 02 Kartasura Tahun Pelajaran 2014/ 2015 - Hananto, Rahadiyan Bayu, Drs. Ariyanto, M.Pd (2015)
This study aimed to describe the improvement of students' mathematics learning outcomes by implementing the strategy of Problem Based Learning (PBL). This study is a class action or Classroom Action Research (CAR). Data obtained from the teachers and students of class VII A Junior High School 02 Kartasura second semester of academic year 2014 / 2015. The data collection method used is the method of observation, testing, field notes, and documentation. Data were analyzed by comparing the results before and after the act of an act. The validity of the data used is triangulation of sources and methods. The results of research by applying strategies Problem Based Learning (PBL) can improve learning outcomes mathematics class VII A Junior High School 02 Kartasura semester of academic year 2014 / 2015. Improved learning outcomes, (a) the courage students to give ideas or ask in completing problems in learning activities from the initial condition14.29%, 34.29% first cycle and second cycle 71.43%; (b) Cooperation students as a group activity of the initial conditions of 22.86%, 42.86% first cycle and cycle II 85.71; (c) students who meet the initial conditions KKM ≥ 75 34.28%, 54.42% first cycle and the second cycle of 68.57%.